Kompetensi Sosial Dosen Pendidikan Agama Islam Terhadap Pembinaan Kepribadian Mahasiswa - Chairullah Chairullah (2021)
Lecturers must have social competence because they are role models for their students. It is often found that the role of lecturers is only to teach and escape from instilling a sense of social and personality to their students. Moving on from these problems, the problems studied in this discussion are related to the implementation of lecturer's social competence in fostering student personality and the application of lecturer's social competence in fostering student personality. This field research is qualitative in nature, data collection techniques through observation, interviews, and documentation. The results of the research; implementation of lecturers by providing exemplary, authoritative, friendly attitude, courtesy, orderly, discipline. Build communication orally and in writing, either directly or indirectly. Active and effective association, social service, community service lecture guidance, visiting and staying in touch with fellow lecturers and students, as well as participating in various socializations, counseling, seminars and so on. Personality development is oriented towards being objective, non-discriminatory and communicating effectively through various social activities, both internal academics, fellow lecturers and students. Deliberation on all issues, coaching is oriented to the ability to adapt and communicate effectively. All of this is a form of student personality development at the PAI Study Program, Faculty of Islamic Religion, Serambi Mekkah University, Banda Aceh.